Relationship between environmental parameters and the plankton community of the Batuhideung Fishing Grounds, - NOVERITA D. TAKARINA; WAWAN NURLIANSYAH; WISNU WARDHANA (Society for Indonesian Biodiversity, 2019)
Takarina ND, Nurliansyah W, Wardhana W. 2019. Relationship between environmental parameters and the planktoncommunity of the Batuhideung Fishing Grounds, Pandeglang, Banten, Indonesia. Biodiversitas 20: 171-180. Phytoplankton has a roleas primary producers and zooplankton as primary consumers in the marine environments. The composition of the plankton communityis dependent on the physical and chemical characteristics of the waters. The aim of the research described here was to analyze thecommunity structure of plankton in the Batuhideung Fishing Grounds, of Banten in Indonesia, and to relate this structure to the physicalparameters (sea surface temperature, clarity, current velocity) and chemical parameters (salinity, pH, DO, nitrate, phosphate) of its seasurroundings. The research was conducted three times at five observation stations from September to October 2017. Samples ofphytoplankton and zooplankton were taken horizontally using nets with mesh size of 80 ?m and 133 ?m, respectively. Results showedthat the sea surface temperature ranged from 28.70-30.20?C, current velocity 0.10-1.30 m/s, clarity 7-10 m, salinity 30-34 g/L, DO 6.20-8.60 mg/L, pH 8.40-8.59, nitrate concentration 0.49-0.81 mg/L, and phosphate concentration 0.09-0.42 mg/L. There were 37 generafrom 4 classes of phytoplankton. The abundance of Bacillariophyta was 52,734 individuals/L, Myzozoa was 1,315 ind/L, Chyanophytawas 633 ind/L, and Euglenophyta was 200 ind/L. There were 35 genera from 12 classes of zooplankton, dominated by Copepods withabundance 82.1-91.4%. The diversity index of phytoplankton ranged from 1.25-2.02, evenness index ranged from 0.52-0.85, anddominance index ranged from 0.19-0.38. Based on multivariate cluster analysis, there were similar environmental parameters in stations1, 2 and 3, while stations 4 and 5 grouped differently from the other three. Based on Pearson's correlation analysis, current velocity andphosphate were positively correlated to phytoplankton abundance, whereas temperature, transparency, salinity, DO, pH, and nitrate werenegatively correlated, temperature significantly so. Nitrate, phosphate, salinity, DO were positively correlated with zooplanktonabundance but not significantly. Temperature, current velocity, clarity, and pH were negatively correlated with zooplankton abundance,but only with pH did the correlation reach statistical significance.